Mother earth, father sky - Harrison, Sue. (New York : Avon Books, 1991)
A young Native American woman, Chagak, watches the brutal destruction of her village by an evil warrior tribe before she embarks on a quest for survival.
1000
Keywords: Glacial epoch -- Fiction; Historical fiction